Corporate Governance, Carbon Emission Disclosure, and Firm Value: A Study of Mining Companies - Yolifiandri, Y.; Kamil, Islamiah; Anjarwati, Sri; Perkasa, Didin Hikmah; Parashakti, Ryani Dhyan (Golden Ratio of Auditing Research, 2025)
This study examines the influence of corporate governance mechanisms and carbon emission disclosure on firm value, specifically in mining companies listed on the Indonesia Stock Exchange. The research focuses on three corporate governance variables: audit committee, independent commissioners, and institutional ownership. It also evaluates the level of carbon emission disclosure based on GRI 305 indicators. Using a purposive sampling, data were collected from 72 observations between 2019 and 2021. Multiple linear regression analysis was employed to assess the relationships between independent variables and firm value, measured using Tobin's Q. The results reveal that the audit committee has a significant positive effect on firm value, indicating that stronger oversight enhances investor confidence. However, independent commissioners, institutional ownership, and carbon emission disclosure were found to have no significant impact on firm value. These findings suggest that while governance practices like active audit committees play a critical role in supporting firm valuation, the market may not fully appreciate other governance elements and environmental disclosures. The study highlights the need for broader stakeholder awareness and regulatory reinforcement regarding the value relevance of environmental transparency and governance practices in high-impact industries like mining.